Hybrid subtractive–additive manufacturing processes for high value-added metal components - Stavropoulos, Panagiotis; Bikas, Harry; Avram, Oliver; Valente, Anna; Chryssolouris, George (International journal of advanced manufacturing technology, 2020)
Hybrid process chains lack structured decision-making tools to support advanced manufacturing strategies, consisting of a simulation-enhanced sequencing and planning of additive and subtractive processes. The paper sets out a method aiming at identifying an optimal process window for additive manufacturing, while considering its integration with conventional technologies, starting from part inspection as a built-in functionality, quantifying geometrical and dimensional part deviations, and triggering an effective hybrid process recipe. The method is demonstrated on a hybrid manufacturing scenario, by dynamically sequencing laser deposition (DLM) and subtraction (milling), triggered by intermediate inspection steps to ensure consistent growth of a part.